An Optimization‐Based Decision‐Support Tool for Post‐Disaster Debris Operations. Issue 6 (17th October 2016) - Lorca, Álvaro; Çelik, Melih; Ergun, Özlem; Keskinocak, Pınar
Abstract : Debris generated by disasters can hinder relief efforts and result in devastating economic, environmental, and health problems. In this study, we present a decision‐support tool employing analytical models to assist disaster and waste management officials with decisions regarding collection, transportation, reduction, recycling, and disposal of debris. The tool enables optimizing and balancing the financial and environmental costs, duration of the collection and disposal operations, landfill usage, and the amount of recycled materials. In addition to post‐disaster operational decisions, the tool can also support the challenging task of developing strategic plans for disaster preparedness. We illustrate the applicability and effectiveness of the tool with a disaster scenario based on Hurricane Andrew.